Preparation of Nanocomposite Plasmonic Films Made from Cellulose Nanocrystals or Mesoporous Silica Decorated with Unidirectionally Aligned Gold Nanorods - Campbell, Michael G. (Materials (Basel), 2014)
Using liquid crystalline self-assembly of cellulose nanocrystals, we achieve long-range alignment of anisotropic metal nanoparticles in colloidal nanocrystal dispersions that are then used to deposit thin structured films with ordering features highly dependent on the deposition method. These hybrid films are comprised of gold nanorods unidirectionally aligned in a matrix that can be made of ordered cellulose nanocrystals or silica nanostructures obtained by using cellulose-based nanostructures as a replica. The ensuing long-range alignment of gold nanorods in both cellulose-based and nanoporous silica films results in a polarization-sensitive surface plasmon resonance. The demonstrated device-scale bulk nanoparticle alignment may enable engineering of new material properties arising from combining the orientational ordering of host nanostructures and properties of the anisotropic plasmonic metal nanoparticles. Our approach may also allow for scalable fabrication of plasmonic polarizers and nanoporous silica structures with orientationally ordered anisotropic plasmonic nanoinclusions.